Aspirations, Poverty and Education: Evidence from India - Pieter Serneels; Stefan Dercon (Institute of Labor Economics (IZA), 2020)
This paper investigates whether aspirations matter for education, which offers a common route out of poverty. We find that mother aspirations are strongly related to the child's grade achieved at age 18. The relation is nonlinear, suggesting there is a threshold, and depends on caste, household income and the village setting. The coefficients remain large and significant when applying control function estimation, using first born son as instrument. A similar strong relation is observed with learning outcomes, including local language, English and maths test results, and with attending school, but not with attending private education. These results are confirmed for outcomes at age 15. The findings provide direct evidence on the contribution of mother aspirations to children's education outcomes and point to aspirations as a channel of intergenerational mobility. They suggest that education outcomes can be improved more rapidly by taking aspirations into account when targeting education programmes, and through interventions that shape aspirations.
Keywords: I25; I21; D03; 330; education; aspirations; poverty